(untitled) (Bangladesh Oncology Journal, 2009)
This retrospective study was done in department of radiotherapy Chittagong Medical College Hospital from 1st January 2007 to 31st December 2007.A total of 2958 patients suffering from cancer had attended the radiotherapy out-patient department ,and among them 1527 (51.62%) were male and 1431 (48.38%) female, with a male/female ratio of 1.06:1. Patients of 6th decades (23.77%) and 7th decade (22.51%) were the main victims followed by 5th decade (20.82%). Among the male, the leading cancers were lung (19.84%), followed by larynx (9.43%), oral cavity (7.92%), esophagus (7.33%), stomach (6.74%) etc. Among the female, breast cancer (15.58%) ranked the topmost position, followed by cervix uteri (11.46%), ovary (6.70%), larynx (6.70%), oral cavity (5.66%), esophagus (5.59%). Among pediatric age group, commonest malignancies were NHL (23.34%), followed by bone tumor (22.22%), retinoblastoma (20.00%). (Bang. Onc. J. 2009; 4 (2) : 44-50)